Integrasi Teknologi Digital dalam Pembelajaran Abad 21: Tinjauan Literatur tentang Penerapan Learning Management System (LMS) di Sekolah Menengah - Suryanti, Tri; Utari, Retno (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2025)
The integration of digital technology into 21st-century learning demands a paradigm shift in education, particularly at the secondary school level, where the use of Learning Management Systems (LMS) is becoming increasingly central. This article presents a literature review that aims to analyze the implementation of LMS in secondary education by focusing on three key aspects: effectiveness, challenges, and pedagogical integration models. The review is conducted through a systematic examination of recent international and national publications addressing LMS use within the context of 21st-century learning. Findings indicate that LMS significantly contributes to enhancing students’ digital competencies, improving the effectiveness of online learning, and fostering 21st-century skills such as collaboration, communication, critical thinking, and creativity. However, its implementation continues to face various challenges, including limited digital literacy among teachers, varying levels of student readiness, infrastructure constraints, resistance to change, and difficulties in embedding LMS into innovative pedagogical strategies. To address these barriers, the study recommends an integrative approach that incorporates the TPACK framework, the SAMR model, and adaptive digital competencies. With the support of appropriate policies, teacher training, and effective managerial strategies, LMS holds strong potential as a transformative tool for building an inclusive, sustainable, and future-oriented 21st-century education ecosystem.